Hydrogen sulfide signaling in plant adaptations to adverse conditions: molecular mechanisms. (2nd June 2021) - Aroca, Angeles; Zhang, Jing; Xie, Yanjie; Romero, Luis C; Gotor, Cecilia
Abstract : This review focuses on recent advances relating to H2 S signaling mechanisms, and highlights interconnections between H2 S and H2 O2 at the post-translational modification level and with ABA in stomatal movement. Abstract: Hydrogen sulfide (H2 S) is a signaling molecule that regulates critical processes and allows plants to adapt to adverse conditions. The molecular mechanism underlying H2 S action relies on its chemical reactivity, and the most-well characterized mechanism is persulfidation, which involves the modification of protein thiol groups, resulting in the formation of persulfide groups. This modification causes a change of protein function, altering catalytic activity or intracellular location and inducing important physiological effects. H2 S cannot react directly with thiols but instead can react with oxidized cysteine residues; therefore, H2 O2 signaling through sulfenylation is required for persulfidation. A comparative study performed in this review reveals 82% identity between sulfenylome and persulfidome. With regard to abscisic acid (ABA) signaling, widespread evidence shows an interconnection between H2 S and ABA in the plant response to environmental stress. Proteomic analyses have revealed persulfidation of several proteins involved in the ABA signaling network and have shown that persulfidation is triggered in response to ABA. In guard cells, a complex interaction of H2 S and ABA signaling has also been described, and the persulfidation of specific signaling components seems to be the underlying mechanism.